Penerapan Teknologi Informasi Dalam Pengelolaan Pertanian: Pelatihan Untuk Kelompok Tani Desa Laboy Jaya - Rusnedy, Hidayati; Musridho, Raja Joko; Sari, Resy Kumala (Journal of Social and Community Service, 2024)
The application of Information Technology is one of the efforts to implement the Tri Dharma of Higher Education, namely community service by voluntarily creating an Information System for the Laboy Jaya Village Farmers Group. Lack of understanding of information technology among the public has resulted in the process of collecting, storing and analyzing data being inefficient. In addition, existing agricultural data remains fragmented across various sources and formats, making integration of critical information difficult. Limited access to timely information, such as weather forecasts and market prices, also results in suboptimal agricultural decisions. Additionally, low technological skills among employees create resistance to change and reduce work productivity. To overcome these problems, the solutions offered include intensive and ongoing training on the use of agricultural information systems for the community, development of integrated information systems that integrate various data sources, increasing the accessibility of agricultural information via mobile or web applications, as well as technology skills development programs. By implementing these solutions, it is hoped that the efficiency and effectiveness of agricultural data management will increase, supporting the productivity and welfare of farmers in Kampar Regency.